Arntz, Reiner/Heribert Picht: Einführung in die Terminologiearbeit. Hildesheim, Zürich, New York: Georg Olms Verlag 1989. 344 Seiten. - Mikkelsen, Hans Kristian (HERMES - Journal of Language and Communication in Business, 1991)
No abstract.